Analisis Siyasah Dusturiyah terhadap Peraturan Presiden Nomor 92 Tahun 2025 tentang Kementerian Haji dan Umrah - Estiqomah; Fathul Mu’in; Estiqomah, Fathul Mu’in, Syarif (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the authority of the Ministry of Hajj and Umrah under Presidential Regulation Number 91 of 2025 and to examine it from the perspective of siyasah dusturiyah (Islamic constitutional law). It employs a normative legal research method utilizing statutory and conceptual approaches. Data—comprising primary, secondary, and tertiary legal materials—were gathered through literature review and analyzed qualitatively using a deductive method. The findings indicate that the establishment of the Ministry of Hajj and Umrah represents a government policy designed to enhance the effectiveness of Hajj and Umrah administration by strengthening institutions, improving services, ensuring pilgrim protection, and supervising the conduct of these pilgrimages. From the perspective of siyasah dusturiyah, the establishment of the ministry aligns with the principles of al-masyru'iyyah (legality), maslahah mursalah (public interest/welfare), al-'adalah (justice), and al-amanah (responsibility). However, the exercise of the ministry's authority must remain within the limits prescribed by legislation to avoid overlapping jurisdiction with other institutions or the abuse of power. Consequently, the successful implementation of the Presidential Regulation hinges on the clear delineation of authority, inter-institutional coordination, and the application of accountability and transparency principles in governance.